Consumers’ perceptions of green marketing in the hotel industry - Punitha, S.; Abdul Aziz, Yuhanis; Abd Rahman, Azmawani (Canadian Center of Science and Education, 2016)
This paper attempts to explore the evolution of green marketing in the hotel industry. This study is guided by three research questions: (1) to explore the level of understanding of local and international tourists on green marketing; (2) to gather tourists’ points of view if marketers have failed or they have never really tried to adopt the concept; and (3) to examine the level of awareness of tourists relating to green practices embraced by hotels. Purposive sampling using the Maximum Variation Sampling (MVS) technique is used to capture a wide range of perspectives in selecting the respondents. The discussion reveals that the concept has evolved hastily in developed countries while it is an emerging trend in developing countries like Malaysia. While some hotels have already begun to respond to environmental concerns in the country, the lack of promotions and advertisements have become part of the causes of knowledge non-appearance. This paper further concludes that green marketing concept should not just be adopted as a marketing tactic, but has to be considered with much greater dynamism, as it has ecological and social elements within it.